Rooster Behavior and Laying Breeder Performance in Natural Mating Cages as a Function of Different Rearing Management - Yuqi Chen; Yalan Zuo; Aosui Zhao; Yao Zhang; Shunshun Han; Can Cui; Huadong Yin (Animals)
Natural mating colony cages are crucial in poultry breeding, yet breed-specific management requires further investigation. We evaluated the effects of sex ratios, stocking densities, and cohabitation age on Lohmann Pink-shell breeders’ performance. A total of 6126 birds were randomly allocated to experimental groups with varying ratios (1:8–1:13), densities (582–748 cm2/bird), and cohabitation ages (120/140 days), each containing six replicates. We monitored male mating frequencies at 50 weeks in 1:8 and 1:10 ratio groups. All 120-day-old groups showed delayed production onset and superior male weight compliance (p < 0.01), with reduced egg breakage and increased healthy chick output (p < 0.01). Lower stocking densities (748/694 cm2/bird) showed lower breakage rate and uniformity than 582 cm2/bird (p < 0.05). The 1:10 sex ratio achieved optimal egg production and fertilization rate (p < 0.05). Male mating peaked between 16:00 and 18:00. Optimal parameters were 120-day age of cohabitation, 694 cm2/bird density, and 1:10 sex ratio, providing theoretical guidance for natural mating colony cage development in layer breeding.